Gulen Movement sebagai Counter-Hegemony:: Membaca Kudeta Turki 2016 dengan Pendekatan Neo-Gramscian - Khamami, Akhmad Rizqon (Jurnal Review Politik, 2017)
This article discusses a hegemonic project of Gulen Movement in Turkey. To read this hegemonic project does this article use a neo-Gramscian approach. The accumulation of Gulen Movement triggers a friction between Gulen Movement and the other existing hegemonic block, that of political Islam. The feud of these Islamic groups started when Gulen Movement makes use of an existing neoliberal system, both at the national and international levels, to build its accumulations on economy, social and politic sphere. The success of the accumulation grows Gulen Movement into a counter-hegemonic block which eventually triggered a Turkish coup 15 July 2016.